PERLINDUNGAN KONSUMEN DALAM PELAYANAN AIR MINUM PDAM TIRTA INDRAGIRI HILIR DI KABUPATEN INDRAGIRI HILIR - Ibnu Hajar; Maryati Bachtiar; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
This study discusses about consumer protection in drinking water services of PDAM Tirta Indragiri Hilir in Indragiri Hilir Regency, consumer protection is all efforts that ensure legal certainty to provide protection to consumers. As an institution that provides public services and also at the same time aims to obtain profits, the Regional Drinking Water Company is required to be able to provide the best service for its customers, by providing customer rights as regulated in Law Number 8 of 1999 concerning Consumer Protection. The PDAM must always improve its services by taking steps both internally and externally to provide legal protection for its customers. The purpose of writing this skipsi is, first, to find out the implementation of the responsibility for the service of PDAM Tirta Indragiri Hilir to the community in Indragiri Hilir Regency, secondly to know the PDAM responsibility towards customers who are disadvantaged by water services by PDAM Tirta Indragiri Hilir. The type of legal research used by the author is a type of sociological legal research that is research that wants to see the correlation between law and society, so as to reveal the effectiveness of the validity of law in society. This research was conducted at the Regional Water Company of Tirta Indragiri Hilir, Indragiri Hilir Regency. Sociological legal research uses primary data and secondary data, while the population and samples are parties related to the problem under study, namely the PDAM Tirta Indragiri Hilir and the community as consumers of PDAM Tirta Indragiri Hilir. The technique of collecting data in this study was library research, interviews and questionnaires. From the results of this study the author concludes that the responsibility of the businessman of PDAM Tirta Indragiri Hilir in providing clean water needs in Indragiri Hilir Regency has not been carried out optimally, the availability and needs of water in Indragiri Hilir Regency are still difficult to do, the form of responsibility carried out by the Actor The business of PDAM Tirta Indragiri Hilir which has caused losses to the community is by installing Pam Plow Meter and Browsing, installing the Water Meter (WM) for the parent and will replace Nseveral subscription Water Meter connections, will cooperate with PT. Setia Mandala Surabaya for water treatment and with PT. Nafarij Jakarta and PT. POS Indonesia (Persero) Tembilhan Post Office to improve the quality of technology- based performance. Keywords: Consumer Protection - Regional Water Company Tirta Indragiri Hilir - Consumer